Multimodal Treatment Approaches Improve Outcomes for Athletes with Comorbid ADHD and Sport-Related Concussions : A Systematic Review - Awalludin, Muchammad Rizky; Dio, Rosalina; Putri, Sheva Shevira Ramadhan Eka; Widayanti , Silvi; Az-Zahid , Umar Faiz; Hasanah , Uswatun; Pradani , Vanesa Irul; Agatha , Zaskia Reysha; Thalia , Zherly Freya; Ugsang Acob, Joel Rey (Tarqabin Nusantara Group, 2024)
Athletes with comorbid attention-deficit/hyperactivity disorder (ADHD) and sport-related concussions (SRC) face unique challenges due to overlapping symptoms that complicate recovery. Multimodal treatment approaches, combining pharmacological, psychological, and physical rehabilitation strategies, have been proposed to address these complexities and optimize outcomes. This systematic review was conducted following PRISMA guidelines to evaluate the effectiveness of multimodal interventions in improving recovery for this population. Relevant studies were identified through a comprehensive search across multiple databases, applying rigorous inclusion and exclusion criteria. Findings indicate that multimodal approaches significantly enhance cognitive function, emotional stability, and physical recovery compared to single-modality treatments. Interdisciplinary care, tailored interventions, and athlete-centered strategies were identified as critical components of effective management. However, challenges such as adherence variability and limited access to specialized resources remain. These results emphasize the importance of integrating multimodal frameworks into clinical practice. Future research should focus on developing standardized protocols and assessing long-term outcomes to ensure sustainable recovery.